2022
DOI: 10.1111/rda.14303
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ultrasound‐guided oocyte retrieval in cattle: State‐of‐the‐art and its impact on the in vitro fertilization embryo production outcome

Abstract: Like any other commercial activity, livestock and seedstock producers pursue regular industry objectives: maximize efficiency and productivity, create value and keep the company profitable. To reach these objectives, various reproductive technology tools have been developed for cattle. Artificial insemination (AI) and embryo technologies (in vivo and/or in vitro) contribute to breeding goals and increase farm productivity through the improvement of specific traits by guided mating (Lamb et al., 2016;Moore & Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 159 publications
2
7
0
1
Order By: Relevance
“…In this regard, it is of particular interest to increase the efficiency of OPU/IVP in terms of the quantitative and qualitative characteristics of the retrieved cumulus-oocyte complexes (COCs) (L.B. Ferré et al, 2023). To improve the efficiency of OPU, various approaches are used: optimization of the technical parameters of OPU; conducting OPU at a certain stage of follicular growth and development; increasing the number of simultaneously growing and maturing follicles through the use of gonadotropins; the use of biomarkers and DNA-markers for the selection of donor cows.…”
Section: схемы гормональной обработки используемые для суперстимуляци...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is of particular interest to increase the efficiency of OPU/IVP in terms of the quantitative and qualitative characteristics of the retrieved cumulus-oocyte complexes (COCs) (L.B. Ferré et al, 2023). To improve the efficiency of OPU, various approaches are used: optimization of the technical parameters of OPU; conducting OPU at a certain stage of follicular growth and development; increasing the number of simultaneously growing and maturing follicles through the use of gonadotropins; the use of biomarkers and DNA-markers for the selection of donor cows.…”
Section: схемы гормональной обработки используемые для суперстимуляци...mentioning
confidence: 99%
“…Однако многообразие протоколов гормональной обработки и различия в ответе на суперстимуляцию в зависимости от индивидуальных особенностей доноров требуют оптимизации протоколов с учетом породы, возраста и физиологического состояния животных. Перспективно использование биомаркеров(108)(109)(110). Так, R. Kowsar с соавт (111).…”
unclassified
“…Studies on different animal models conceived by ICSI have shown an asynchronous remodeling of chromatin decondensation of the male pronucleus in primates, cattle, and mice [123][124][125]. ICSI-conceived mice compared to conventional IVF-conceived counterparts present long-lasting transcriptome disturbances that are maintained until the neonatal stage.…”
Section: Effects Of Icsi On Epigenetic Alterationmentioning
confidence: 99%
“…Ovum pick-up (OPU) and in vitro fertilization (IVF) are used in cattle to accelerate the diaspora of genotypes and genetically superior females [1],furthermore, they enable the multiplication of small populations adapted to adverse environments and even in danger of extinction [2]. OPU-IVF has been successful for Bos taurus breeds in the temperate climatic region and for Bos indicus breeds in the hot climatic tropical region [3,4].…”
Section: Introductionmentioning
confidence: 99%